The examination of secondary school students’ awareness and knowledge levels about substance addiction - Özay Köse, Esra; Gül, Şeyda; Keskin, Bülent (Journal of Dependence, 2017)
Objective: The aim of this study is to determine the secondary school students’ awareness and knowledge levels about addictive substances that widely used among adolescents, and also examine the correlation between these two variables. Method: The study was survey method. The study was implemented under biology course with total of 338 students who attended to 9-12th grade from secondary school in Erzincan. The data collection tools were Substance Addiction Knowledge Test (SAKT) that developed by the researchers and Substance Addiction Awareness Scale (SAAS). The data were analyzed with mean score, standard deviation and total score values by using SPSS 16.0 program. And also, Pearson correlation was used to determine the relationship between the variables. Results: The findings indicated that the students had high score for substance addiction awareness levels, but their knowledge levels were in intermediate level. A positive but weak correlation was determined between substance addiction awareness and knowledge level. Conclusion: The effect of narcotics on system and organs should be touched upon during teaching of health issues of system in biology courses. In addition to the situation determination studies about substance addiction, the studies should be done for the improvement of the students in this subject.